Variations in the Motivations of Environmental Citizen Scientists. (5th May 2021) - West, Sarah; Dyke, Alison; Pateman, Rachel
Understanding motivations is important because appealing to and fulfilling motivations helps citizen science projects recruit and retain participants. We summarise the literature around motivations, drawing on key theories from volunteering more broadly and building on this with additional motivations identified in studies of citizen scientists. We also examine what is known about differences in motivations between demographic groups. We then report on a survey of 613 environmental citizen scientists in Great Britain; they were asked to select from a list of motivations derived from the literature. We used hierarchical cluster analysis to group respondents by types of motivations held. Two clusters were dominated by people holding Values motivations (concern for others or the environment), both of which had high proportions of older people and people identifying as from white ethnic groups. A third cluster included people with Egoism motivations (participating to learn something or further one's career) and Values motivations. This cluster had a higher proportion of some commonly underrepresented groups than the overall sample, including younger people, people identifying as from minority ethnic groups and people in lower socioeconomic groups. Two further clusters also had higher proportions of people from minority ethnic groups than the overall sample, one dominated by those who participated because they were asked to, and the other by people who held other motivations not in our list. We use insights on participant motivations from the literature and survey to make recommendations to those wishing to recruit and retain citizen scientists, particularly those from underrepresented groups.